Effect of Expanded Perlite and Exfoliated Vermiculite Aggregate Additives on Water Vapor Permeability Performance of Cement-Based Lightweight Mortars - Lütfullah Gündüz; Sevket Onur Kalkan (Journal of Sustainable Construction Materials and Technologies, 2025)
Vapor diffusion is the movement of water vapor molecules through porous materials such as wood, insulation products, and lightweight wall elements due to differences in vapor pressure. Vapor retarders are used to control vapor diffusion through wall sections and surfaces. All building materials provide some resistance to vapor diffusion, and the amount of resistance varies depending on the material’s properties. These properties can vary with relative humidity and moisture content, age, temperature, and other factors. Vapor resistance is usually expressed using the inverse term of “vapor permeability,” which is the relative ease of vapor diffusion through a material. Water vapor permeability in building materials is an essential factor that allows moisture formed indoors in a building section to pass to the outside and prevents damage from moisture inside. Condensation that may occur inside and/or on the surface of a building section due to inadequate water vapor diffusion negatively affects heat transfer in building materials and reduces insulation performance. The type of aggregate used in cement-based mortars is an essential factor influencing the water vapor permeability of the mortar. The water vapor permeability of normal-density aggregate mortars is lower than that of lightweight aggregate mortars. In this study, a series of cement-based composite mortar designs using expanded perlite and expanded vermiculite aggregates were created, and in addition to physical and mechanical analyses, water vapor permeability properties were also comparatively investigated according to the control mortar sample. In the mix designs, 32% expanded perlite and exfoliated vermiculite aggregates were used as lightweight aggregates. As expanded perlite aggregate, two different characteristic aggregates expanded under the effect of 765 °C and 985 °C were used. As vermiculite aggregate, two characteristic aggregates with 55% and 85% opening phenomenon under expansion temperature were used. According to the study results, water vapor resistance coefficients varied between 3.40 and 6.70 for lightweight aggregate test samples. It has been observed that the high expansion/opening rates in the production of materials used as lightweight aggregates cause lower water vapor resistance coefficients of cement-based mortars obtained with these materials.